W.H. Auden: a study of his poetry and its critics, 1930-1960 - Millard, Geoffrey Charles (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1971)
How does a poet fare nowadays at the hands of his critics? This study examines the critical reception Auden received from 1930 to 1960; through a close consideration of a selection of the poems written in this period it will be demonstrated that a considerble discrepency exists between Auden's poetic achievement and. the criticism it received. The main reason for this discrepancy is the lack of attention to individual poems in favour of sweeping surveys of a volume of poetry or the poet's total output. The core of the thesis lies here and the thesis as a whole derives from concern for a poet's reputation during his poetic career.
Keywords: Auden, W. H., (Wystan Hugh), 1907-1973 -- Criticism and interpretation; English poetry -- 20th century -- History and criticism